Distinct roles of Tfap2A & Tfap2B in the diversification of GABAergic neuronal subtypes in the cerebellum - Norliyana Zainolabidin (2017)
The cerebellum plays a critical role in sensory-motor integration and is important for precise coordination of body, limb and eye movements as well as adaptation and learning of motor skills. The ability of the cerebellum to carry out these tasks relies on the faithful production and assembly of various classes of cerebellar neurons into functional circuits during development. The distinct subtypes of inhibitory neurons are important in providing feedforward and feedback inhibition to the cerebellar circuit. To explore the molecular mechanisms underlying the development of cerebellar inhibitory neurons, we examined the involvement of Tfap2A and Tfap2B in the specification of cerebellar progenitors into distinct inhibitory neuronal subtypes in mice. We show, for the first time, that Tfap2A and Tfap2B are expressed in distinct subsets of cerebellar inhibitory neurons during embryonic development, and that their expression persists into adulthood. The developmental expression pattern of Tfap2A and Tfap2B suggests that these transcription factors might play a role in the specification of GABAergic neuronal subtypes in the developing cerebellum and may continue to regulate the maintenance and refinement of inhibitory circuits in the mature cerebellar cortex. We carried out in utero electroporation and in vivo lentiviral transduction to investigate consequences of manipulating the expression of these transcription factors on specification of GABAergic neuronal subtypes.